Design of a Discrete Tracking Controller for a Magnetic Levitation System: A Nonlinear Rational Model Approach. (19th March 2015) - Gómez-Salas, Fernando; Wang, Yongji; Zhu, Quanmin
Abstract : This work proposes a discrete-time nonlinear rational approximate model for the unstable magnetic levitation system. Based on this model and as an application of the input-output linearization technique, a discrete-time tracking control design will be derived using the corresponding classical state space representation of the model. A simulation example illustrates the efficiency of the proposed methodology.